Selection of nonpathogenic ethyleneproducing rhizobacteria for accelerated depletion of Striga hermonthica seed bank - Ahonsi, M.; Berner, D.; Emechebe, A.; Sanginga, N.; Lagoke, S.T.O. (2002)
Three Pseudomonas syringae pathovar glycinea (Psg) strains known to produce large amounts of ethylene were tested for efficacy in germinating seeds of Striga hermonthica (Del.) Benth. in a laboratory, as were 312 rhizosphere isolates of non-pathogenic fluorescent Pseudomonas spp. and 38 Bradyrhizobium japonicum isolates. Strains of Psg were 67% as effective as GR-24, and 31 and 38% more effective than ethylene gas (2.5 mg per Petri dish) and root pieces of the best soybean cultivar (SAMSOY-2), respectively. None of the non-pathogenic pseudomonas and rhizobial isolates effectively germinated S. hermonthica seeds compared with Psg strains. Our results indicate that ethylene producing bacterial strains can be highly effective in germinating S. hermonthica seeds and suggest that such bacteria have potential as bio-control agents of this parasitic plant in Africa. However, ethylene production by bacteria may be linked with pathogenic ability. This suggests that gene modification and transfer technology may be necessary to exploit the potential usefulness of ethylene-producing bacteria for S. hermonthica control.